2007
DOI: 10.1017/s0266467407003975
|View full text |Cite
|
Sign up to set email alerts
|

Bruchid beetle infestation and the value of Attalea butyracea endocarps for neotropical rodents

Abstract: Frugivorous and granivorous vertebrates often discriminate against seeds and fruits infested by insects (Sallabanks & Courtney 1992). Insects may actively render seed or fruit unpalatable or unusable to vertebrates as a strategy to maximize the amount of food available to themselves (Janzen 1977). Nevertheless, vertebrates sometimes do not differentiate between sound and infested seeds or fruits (Dixon et al. 1997, Weckerly et al. 1989), or even prefer insect-infested seeds and fruits to sound ones (Sallab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 24 publications
2
42
0
3
Order By: Relevance
“…and Proechimys spp., were difficult to identify and therefore were gathered in a single group. Because small holes are indicators of insect predation, we also noted holes in the endocarp (Silvius, & Fragoso, 2002;Galvez, & Jansen, 2007). We recorded rotten, attacked by fungus or nonviable seeds, based on the exterior seed appearance and finally the inviability of the seed.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…and Proechimys spp., were difficult to identify and therefore were gathered in a single group. Because small holes are indicators of insect predation, we also noted holes in the endocarp (Silvius, & Fragoso, 2002;Galvez, & Jansen, 2007). We recorded rotten, attacked by fungus or nonviable seeds, based on the exterior seed appearance and finally the inviability of the seed.…”
Section: Study Sitementioning
confidence: 99%
“…When dispersed long distances, seeds had higher survivorship with lower interspecific competition and invertebrate infestation; e.g., Coleoptera; Bruchids, Scolytine. (Janzen, 1970;Quiroga-Castro, & Roldán, 2001;Galetti, Donatti, Pires, Guimarães, & Jordano, 2006;Galvez, & Jansen, 2007;Dracxler et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the endocarps of A. butyracea, Gálvez and Jansen (2007) found indirect evidence that rodent foragers do not discriminate between infested and non-infested endocarps. This result is superficially surprising considering the fact that on average, seeds contain more energy than larvae.…”
Section: Introductionmentioning
confidence: 96%
“…Gálvez and Jansen's study suggested that rodents show no preference for either type of endocarp because of a trade-off effect; the infested endocarps with less energy can be opened more easily than the non-infested endocarps that contain higher energy content. Building on the study by Gálvez and Jansen (2007), I studied the trade-off hypothesis and compared the relationship of metabolizable energy content over time of handling (M/t) for both types of endocarps.…”
Section: Introductionmentioning
confidence: 99%